2000
DOI: 10.1017/s0952836900003149
|View full text |Cite
|
Sign up to set email alerts
|

Winter selection of habitats within intertidal foraging areas by mink (Mustela vison)

Abstract: Patterns of habitat selection by American mink Mustela vison within foraging areas located on the shore, were studied in a coastal environment of Scotland from November to March in 1983March in /84, 1984March in /85 and 1994. The abundance of prey in the intertidal zone was modelled in relation to abiotic environmental characteristics. Four factors were found to be important predictors of prey abundance: the position within the tidal zone, the abundance and size of rockpools, the nature of the substratum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The data used in this study were instead mostly from the winter and spring seasons, when resources were scarcer (Kruuk 1995) and competition was likely to be more intense. The lower niche overlap in the Scottish Islands might also be partly due to the fact that in coastal habitats, where the study of Clode and Macdonald was conducted, mink tend to hunt in the intertidal area while otters hunt in the sea (Bonesi et al 2000), thereby favouring the selection of different prey species and consequently a lower niche overlap. Instead, in a riparian habitat, such as the one of this study, both otter and mink feed in the same areas and therefore are likely to catch more of the same prey.…”
Section: Discussionmentioning
confidence: 99%
“…The data used in this study were instead mostly from the winter and spring seasons, when resources were scarcer (Kruuk 1995) and competition was likely to be more intense. The lower niche overlap in the Scottish Islands might also be partly due to the fact that in coastal habitats, where the study of Clode and Macdonald was conducted, mink tend to hunt in the intertidal area while otters hunt in the sea (Bonesi et al 2000), thereby favouring the selection of different prey species and consequently a lower niche overlap. Instead, in a riparian habitat, such as the one of this study, both otter and mink feed in the same areas and therefore are likely to catch more of the same prey.…”
Section: Discussionmentioning
confidence: 99%
“…Interspecific aggression and killing is, indeed, common among mammalian carnivores (Palomares and Caro 1999) and such behaviours have been observed also between otters and mink. Otters have been observed stealing food from mink (Bonesi et al 2000) and mink fur has been found in otter spraints indicating that otters are able to predate on mink (Grigor'ev and Egorov 1969).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of otters, mink diet becomes more terrestrial yet the diet of otters changes relatively little in response to the presence of mink, suggesting that, as expected from their relative sizes, otters are the dominant competitor and that where they are sympatric, mink are forced to undergo a dietary niche shift (Clode andMacdonald 1995, Bonesi et al 2004). Otters have been observed stealing food from mink (Bonesi et al 2000), and bite wounds in otters apparently inflicted by mink suggest that direct aggres-sion occurs between them (Simpson 2006). Indeed, field signs indicate that the presence of mink have declined nationally in recent years, in apparent response to a concomitant increase in the signs of otters (Strachan and Jefferies 1996, Jefferies 2003, Bonesi et al 2006, McDonald et al 2007, and evidence suggests that mink densities may decline as otters recover (Bonesi and Macdonald 2004a).…”
Section: Introductionmentioning
confidence: 99%